Extending the in vivo persistence of synthetic glycoconjugates using a serum-protein binder. Issue 10 (1st September 2022) - Daskhan, Gour Chand; Motyka, Bruce; Bascom, Roger; Tran, Hanh Thuc; Tao, Kesheng; West, Lori J.; Cairo, Christopher W.
Abstract : A strategy for augmenting multivalent glycoconjugates with a serum-protein recognition element extends half-life in vivo and maintains engagement with lectin receptors. Abstract : Synthetic glycoconjugates are used in the development of vaccines and the design of inhibitors for glycan–protein interactions. The in vivo persistence of synthetic glycoconjugates is an important factor in their efficacy, especially when prolonged interactions with specific cell types may be required. In this study, we applied a strategy for non-covalent association of an active compound with serum proteins for extension of glycoconjugate half-life in serum. The small molecule, AG10, has previously been used to extend the half-life of small molecules through its high affinity for transthyretin (TTR), a serum protein. Using a tetravalent polyethylene glycol (PEG)-based scaffold we developed a synthetic strategy for glycoconjugates that allowed for controlled addition of multiple tags, such as a TTR affinity tag or fluorophore. We designed a version of AG10 modified at the pyrazole core, named GD10, amenable to our conjugation strategy and introduced to glycoconjugates using a tri-functional linker. This approach allowed for attachment of GD10 and fluorophore tags, as well as carbohydrate antigens. We then tested the influence of the GD10 tag on glycoconjugate half-life in vivo using a mouse model. Our results suggest that the combination of the GD10 tag and the PEG scaffold extended the half-life of glycoconjugates by as much as 10-fold when compared to proteins of similar molecular weight. The GD10 tag was able to extend the half-life of similar glycoconjugates by as much as 2-fold. We observed a role for the terminal saccharide residue of the carbohydrate antigen and confirmed that conjugates were able to penetrate multiple compartments in vivo including bone marrow, lymph nodes, and other organs. The introduction of the GD10 tag did not obstruct the ability of conjugates to interact with lectin receptors. We conclude that serum protein binders can be used to extend the persistence of glycoconjugates in vivo .